Peningkatan Kemampuan Profesional Guru SMK melalui Pelaksanaan Supervisi Pengajaran di Minahasa Selatan - Vidlina Lie; Joulanda A.M Rawis; Mozes Markus Wullur; Viktory N.J. Rotty (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to determine the implementation of the teaching supervision work program, and the obstacles faced by school principals in the implementation of teaching supervision. In order to achieve the research objectives, the researchers used a qualitative approach. Data collection techniques were carried out in several ways, namely interviews, observations, and documentation studies. Data analysis methods used are data reduction, visualization and verification. The subjects of this study were principals, vice principals and teachers. After carrying out the research steps, it was found that the results of the study showed that: (1) The principal teaching supervision work program for Vocational High Schools in South Minahasa already had a standardized design for the next one year period and was planned to be reformulated next year; (2) The implementation of teaching supervision applied by the head of SMK in South Minahasa is carried out with two approaches, namely the indirect and direct approach; and (3) Obstacles faced by school principals in implementing teaching supervision include: (a) The principal has very little implementation time so that the implementation of supervision is difficult to schedule, (b) teaching supervision techniques, focusing more on the psychological aspects of teachers and other factors. This greatly determines the course of the implementation of the teaching supervision program, and (c) the behavior of teachers when supervising teaching is carried out, the conditions of the teachers are very heterogeneous and highly dependent on the techniques used by the principal. Keywords: Teaching Supervision, Teacher Professionalism Improvement, Principal Penelitian ini bertujuan untuk mengetahui pelaksanaan program kerja supervisi pengajaran, dan hambatan yang dihadapi kepala sekolah dalam pelaksanaan supervisi pengajaran. Dalam rangka mencapai tujuan penelitian tersebut maka peneliti menggunakan pendekatan kualitatif. Untuk teknik pengumpulan data dilakukan melalui beberapa cara yaitu wawancara, observasi, dan studi dokumentasi. Metode analisis data yang digunakan adalah reduksi data, visualisasi dan verifikasi. Subjek penelitian ini adalah kepala sekolah, wakil kepala sekolah dan guru-guru. Setelah melaksanakan langkah-langkah penelitian maka ditemukanlah hasil penelitian dimana menunjukkan bahwa: (1) Program kerja supervisi pengajaran kepala sekolah untuk SMK di Minahasa Selatan sudah memiliki rancangan yang sesuai standart untuk jangka waktu satu tahun ke depan dan direncanakan akan dirumuskan kembali tahun depan; (2) Pelaksanaan supervisi pengajaran yang diterapkan oleh kepala SMK di Minahasa Selatan dilaksanakan dengan dua cara pendekatan yaitu pendekatan tidak langsung dan langsung; dan (3) Hambatan yang dihadapi kepala sekolah dalam pelaksanaan supervisi pengajaran antara lain: (a) Waktu pelaksanaan sangat sedikit yang dimiliki oleh kepala sekolah sehingga pelaksanaan supervisi sulit untuk diagendakan, (b) teknik supervisi pengajaran, lebih menitikberatkan pada aspek psikologis guru dan faktor ini sangat menentukan jalannya pelaksanaan program supervisi pengajaran, dan (c) perilaku guru pada saat dilakukan supervisi pengajaran, kondisi guru-guru sangat heterogen dan sangat tergantung pada teknik yang digunakan oleh kepala sekolah. Kata Kunci: Supervisi Pengajaran, Profesionalisme Guru, kepala sekolah